490 Relationships of Placental Size with Beef Cow and Calf Characteristics. (10th April 2018) - Stoecklein, K S; Duncan, N B; Meyer, A M
Abstract: Our objective was to investigate the relationship of placental size measures with calf size and sex, as well as cow BW, BCS, and age. Expelled placentas were collected from spring-calving crossbred beef cows and heifers (n = 30; 623.1 ± 15.4 [SE] kg BW, 5.18 ± 0.10 BCS, 3.24 ± 0.45 yr of age), rinsed, and refrigerated until dissection. During dissection, cotyledons were removed from the inter-cotyledonary tissue, cotyledonary and inter-cotyledonary tissues were weighed, cotyledons were counted, and umbilical vessel diameters were measured. After dissection, tissues were dried at a 100°C to determine dry weight. At birth, calf time to stand (time from birth until the calf successfully stood for 5 consecutive seconds), birth weight, and body size measurements (shoulder to rump length, heart girth, and abdominal girth) were recorded. Ponderal index was calculated as calf weight divided by calf length cubed. Pearson correlation coefficients were determined between placental parameters, calf measures, and cow characteristics. The effect of calf sex on placental size was determined using a mixed model. Birth weight had a weak positive correlation with inter-cotyledonary tissue weight ( P = 0.04). Calf heart girth had a moderate positive correlation with whole placenta and cotyledon weight ( P ≤ 0.02) and tended to have a weak positive correlation with inter-cotyledonary tissue and average cotyledon weight ( P = 0.10). There was a moderate positive correlation of abdominal girth with whole placenta and inter-cotyledonary tissue weight ( P ≤ 0.02) and tended to be a weak positive correlation between abdominal girth and cotyledon weight ( P = 0.07). Time to stand tended to have a weak positive correlation with whole placenta and cotyledon weight ( P ≤ 0.08). There was no effect of calf sex on placental size ( P ≥ 0.14). Cow BCS had a moderate positive correlation with inter-cotyledonary tissue weight ( P = 0.02), and tended to have a weak positive correlation with whole placenta weight ( P = 0.06) and weak negative correlation with average vessel diameter ( P = 0.08). Cow BW had a moderate positive correlation with whole placenta, cotyledon, and inter-cotyledonary tissue weight ( P ≤ 0.02). Cow age had a weak positive correlation with number of cotyledons ( P = 0.05) and tended to have a weak positive correlation with inter-cotyledonary tissue weight ( P = 0.06). In conclusion, while calf sex may have no effect on placental size, calf size, as well as cow BW, BCS, and age, have relationships with placental size.